Clinical guidelines for the treatment of congenital diaphragmatic hernia. Issue 4 (13th April 2021) - Ito, Miharu; Terui, Keita; Nagata, Kouji; Yamoto, Masaya; Shiraishi, Masayuki; Okuyama, Hiroomi; Yoshida, Hideo; Urushihara, Naoto; Toyoshima, Katsuaki; Hayakawa, Masahiro; Taguchi, Tomoaki; Usui, Noriaki; et al.
Abstract: Congenital diaphragmatic hernia (CDH) is a birth defect of the diaphragm in which abdominal organs herniate through the defect into the thoracic cavity. The main pathophysiology is respiratory distress and persistent pulmonary hypertension because of pulmonary hypoplasia caused by compression of the elevated organs. Recent progress in prenatal diagnosis and postnatal care has led to an increase in the survival rate of patients with CDH. However, some survivors experience mid‐ and long‐term disabilities and complications requiring treatment and follow‐up. In recent years, the establishment of clinical practice guidelines has been promoted in various medical fields to offer optimal medical care, with the goal of improvement of the disease' outcomes, thereby reducing medical costs, etc. Thus, to provide adequate medical care through standardization of treatment and elimination of disparities in clinical management, and to improve the survival rate and mid‐ and long‐term prognosis of patients with CDH, we present here the clinical practice guidelines for postnatal management of CDH. These are based on the principles of evidence‐based medicine using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. The recommendations are based on evidence and were determined after considering the balance among benefits and harm, patient and society preferences, and medical resources available for postnatal CDH treatment.